CHANGE MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATIONAL INSTITUTIONS - Budiman Budiman (ADISAM Publisher, 2022)
The purpose of this study is to describe the problems of change management in educational institutions and alternative solutions that can be pursued in overcoming these problems. This type of research uses library research. The results of the study show that the problems that often arise in the process of change in educational institutions are resistance to change and temporary change. Several factors causing the failure of the change process are: 1) changes are not planned properly; 2) ignoring the human element in managing change; 3) failure to build strong coalitions to drive change; 4) lack of outreach to internal educational institutions; and 5) the lack of innovation and the powerlessness of the change-sustaining energy. Alternative solutions are: 1) overcoming resistance to change; 2) innovate; and 3) maximizing the energy of change in educational institutions, including HR support, maximum supervision and support from technology and information systems.